SCIENTIFIC AND METHODOLOGICAL APPROACHES TO IDENTIFYING THE CORE ESSENCE OF PUBLIC ADMINISTRATION OF A REGIONAL INVESTMENT AND CONSTRUCTION COMPLEX - Prav Yu. (Theory and Practice of Public Administration, 2019)
Construction industry can be regarded as integrating various activity types of sectoral and cross-sectoral nature and is a key industry in the investment field as it is directly linked to setting up a basis of material production in the form of buildings, works, power and transport mains, communication systems, etc. In all these activities, the priority lies with not so much creating a specific economic benefit as arranging an investment and construction process.Administration of investment processes in the region encounters a string of problems caused by factual absence of a concept and mechanism of regional influence on the investment field, insufficient readiness of regional governing agencies to regulate the investment process due to underdeveloped informational support and diagnostics and a low level of the evaluation basis of such interference with the economic sector, as well as losing the organizational and administrative structures of cross-sectoral development of the economy on a progressive technological basis in the course of economic reforms. Thus, improving public mechanisms of administering the investment and construction complex in a region is impossible without researching the theoretical and methodological bases and core of investments, investment and construction activities and public administration of a regional investment and construction complex, identifying the factors affecting the investment and construction process, etc.A sizable contribution in solving the issues of administering the investment and construction complex, which are linked to market competition in this field, has been made by A. Asaul, N. Asaul, A. Alekseyev, A. Lobanov, Ye. Vylhin, L. Hryhoryeva, O. Darushyn, M. Dmytriyev, B. Shchurov, S. Koshechkyn, O. Kovalevska, Ya. Zhalilo, Ya. Bazyliuk, Ya. Belinska, A. Tkachenko, Ye. Plaksina, et al. Besides, in modern-day circumstances, the concept of investment and construction complex corresponds more to the contents of economic relations in the sector being studied than the concept of administering the investment complex. It is the investment and construction complex that should be object of the state’s regulating influence. Article’s purpose is to specify scientific and methodological approaches to identifying the core essence of public administration of the investment and construction complex in a region and its categorical and conceptual analysis. The article reviews scientific and methodological approaches to identifying the core essence of public administration of the investment and construction complex in a region. The author analyzes the existing concepts and suggests his view of the essence of the following: “investments,” “investment complex,” “investment and construction activities,” “investment and construction field,” “investment and construction complex,” “public administration of the regional investment and construction complex.” It is determined that activities of the investment and construction complex can be characterized by the following basic directions: design of investment projects; production of building materials and structures; construction of facilities, works, and capacities; formation of utility infrastructure; funding of investment project implementation; providing the investment projects with land lots for construction sites. It is ascertained that improving public mechanisms of administering the investment and construction complex in a region is impossible without researches into theoretical and methodological grounds and core of investments, investment and construction activities, and identifying the factors affecting the investment and construction process. The essence of regional administration of the investment and construction complex is a specifically organized territorial combination of construction operations and results of their economic operations with regional and sectoral administration and consists in deliberate alteration of contents and essence of its parts, existing proportions, and relations between them in order to enhance its performance and improve quality of the population’s life on these grounds. And eventually, it is proposed to identify public administration of the regional investment and construction complex as a process of managing all aspects of investment operations at the state level with legislative and regulative methods; at the regional level of administering investment programs and projects; and managing the investment activities of an individual economic operator.